Assessment of Family Planning Services at Community Pharmacies in San Diego, California - Sally Rafie; Grace Yeoul Kim; Lily M. Lau; Connie Tang; Colette Brown; Nicole Monastersky Maderas (MDPI AG, 2013)
Levonorgestrel emergency contraception and other contraceptive methods are available over-the-counter (OTC); however youth continue to face a number of barriers in accessing healthcare services, including lack of knowledge of the method, fear of loss of privacy, difficulties in finding a provider, and cost. A descriptive, nonexperimental, cross-sectional study of a sample of 112 community pharmacies in San Diego, California was conducted between December 2009 and January 2010 to assess community pharmacy practices related to the availability and accessibility of family planning health pharmacy services and products, particularly to youth. A majority (n = 79/112, 70.5%) of the pharmacies carried a wide selection of male condoms; however, the other OTC nonhormonal contraceptive products were either not available or available with limited selection. A majority of the pharmacies sold emergency contraception (n = 88/111, 78.6%). Most patient counseling areas consisted of either a public or a semi-private area. A majority of the pharmacy sites did not provide materials or services targeting youth. Significant gaps exist in providing family planning products and services in the majority of community pharmacies in San Diego, California. Education and outreach efforts are needed to promote provision of products and services, particularly to the adolescent population.